Au nanoparticle-modified WO3 nanoflowers/TiO2 nanotubes used for the SERS detection of dyes. (27th October 2017) - Zhang, Bing; Yin, Xuehua; Zhen, Deshuai; Gu, Wenhong; Liu, Yingju; Cai, Qingyun
Abstract : WO3 nanoflowers were successfully fabricated for the first time on a TiO2 nanotube substrate via a hydrothermal method. Abstract : A metal–semiconductor heterojunction material was synthesized by electrodepositing Au nanoparticles onto the surface of WO3 nanoflowers that were grown on TiO2 nanotubes and applied, for the first time, to the surface-enhanced Raman scattering (SERS) detection of dyes. Owing to their nanoflower structure, a localized surface plasmon resonance was generated on the surface of the Au/WO3 /TiO2 nanosheets, which brings about multiple enhanced three-dimensional electromagnetic fields. An enhanced factor of 3.6 × 10 6 was achieved. The spot-to-spot change in the SERS intensity was less than 15% and the SERS substrate could be preserved for at least 50 days. The analysis of dyes in real samples provided a recovery rate of 94.33–115.6%, indicating its potential applications in environmental analysis.